The position of pre-marital gift as matrimonial property in Malaysia - Ibrahim, Norliah; Halim, Akmal Hidayah (Sweet & Maxwell Asia, 2013)
Is gift a matrimonial property? The question frequently arises in court in the context of division of matrimonial property between a husband and wife upon divorce where couples may fight about these very gifts that were once given out of love. It is argued that generally, gift is not considered as a matrimonial property even though it is acquired during the marriage as it is of common understanding that the donor intends to benefit the donee by disposing of the property as a gift which is normally done out of love and affection. However, some decided cases have shown that gift may be subject to division upon divorce if it has been substantially improved during the marriage since it complies with related provisions dealing with the division of matrimonial property upon divorce. Hence, this paper seeks to discuss the position of gift in cases where the claim on the division of matrimonial property arises upon divorce by analyzing relevant provisions relating to the claim of matrimonial property and the decided cases on the qualification of gift as a subject to such claim. The paper concludes that since the purpose of the division of matrimonial property is mainly to divide the marital gain of the marital relationship, it should not include a gift which is a kind of windfall and not literally acquired by the party to the marriage.